ผลของโปรแกรมการบำบัดทางความคิดบนพื้นฐานของการเจริญสติต่อความวิตกกังวลในผู้ป่วยโรควิตกกังวลทั่วไป - พัชรินทร์ ครองธรรม (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This research is a quasi-experimental pretest-posttest control group design. The objectives were to compare: 1) state and trait anxiety of patients with generalized anxiety disorder before and after received the mindfulness-based cognitive therapy program, and 2) state and trait anxiety of patients with generalized anxiety disorder who received mindfulness-based cognitive therapy program and those who received regular nursing care. The samples of 40 patients with generalized anxiety disorder, who met the inclusion criteria, were receiving services in out-patient department, psychiatric clinic in King Chulalongkorn Memorial Hospital. They were matched-pairs by gender and anxiety scores and then randomly assigned to either the experimental or control groups, 20 subjects in each group. The experimental group received the mindfulness-based cognitive therapy program, while the control group received regular nursing care. Research instruments comprised of: 1) the experimental tool is the mindfulness-based cognitive therapy program, 2) data collection tools including demographic data form and the State-Trait Anxiety Inventory form Y, and 3) the experimental monitoring tool is the Ruminative Response Scale. The content validity of the 1st and 3nd instruments had verified by 5 professional experts. The STAI form Y-1, the STAI form Y-2 and Ruminative Response Scale had Cronbach’s Alpha reliability as of .87, .88 and .85, respectively. Descriptive statistics and t-test were used in data analysis. The conclusions of this research are as follows: 1. the mean scores on state and trait anxiety of the experimental group after received the mindfulness-based cognitive therapy program was significantly lower than that before at the .05 level; 2. the mean scores on state and trait anxiety of the experimental group after received the mindfulness-based cognitive therapy program was significantly lower than those who received regular nursing care, at the .05 level.